Simulation of Roundness, Hardness and Microstructure of Bearing Rings with Thin Cross Sections by Using Sysweld - Fabian, Peter; Jankejech, Peter; Kyselova, Martina (Communications - Scientific letters of the University of Zilina, 2014)
The roller bearing is a component which helps to reduce friction on relative rotational or sliding movements of the machine parts. Nowadays, there are many kinds of rolling bearings whose production is constantly improving due to increasing demands on the mechanical properties and durability. An important and necessary step in the production of rolling bearings is the heat treatment. Technological heating process must be created rationally for the required mechanical properties such as hardness, toughness and also dimensional accuracy all with respect to the economic efficiency. Because of the economical demands, simulation software is increasingly beginning to be used in the projection of heat treatment. This simulation software can predict metallurgical and mechanical properties of components after heat treatment, and thus it is easier to select the optimal material design, heat treatment process and it can possibly identify construction deficiencies in the selected part. For simulation of the heat treatment the SWYSWELD software from ESI group was used. As the output value after the simulated heat treatment (quenching) was hardness, composition of microstructure, roundness and residual stresses. These results of the simulation were then compared with the real measured values [1, 2 and 3].